Twelve-Month Cognitive Trajectories in Individuals at Ultra-High Risk for Psychosis: A Latent Class Analysis. Issue 1 (13th January 2022) - Allott, Kelly; Schmidt, Stefanie J; Yuen, Hok Pan; Wood, Stephen J; Nelson, Barnaby; Markulev, Connie; Lavoie, Suzie; Brewer, Warrick J; Schäfer, Miriam R; Mossaheb, Nilufar; Schlögelhofer, Monika; Smesny, Stefan; et al.
Abstract: Understanding longitudinal cognitive performance in individuals at ultra-high risk for psychosis (UHR) is important for informing theoretical models and treatment. A vital step in this endeavor is to determine whether there are UHR subgroups that have similar patterns of cognitive change over time. The aims were to: i) identify latent class trajectories of cognitive performance over 12-months in UHR individuals, ii) identify baseline demographic and clinical predictors of the resulting classes, and iii) determine whether trajectory classes were associated with transition to psychosis or functional outcomes. Cognition was assessed using the Brief Assessment of Cognition in Schizophrenia (BACS) at baseline, 6- and 12-months ( N = 288). Using Growth Mixture Modeling, a single unimpaired improving trajectory class was observed for motor function, speed of processing, verbal fluency, and BACS composite. A two-class solution was observed for executive function and working memory, showing one unimpaired and a second impaired class. A three-class solution was found for verbal learning and memory: unimpaired, mildly impaired, and initially extremely impaired, but improved ("caught up") to the level of the mildly impaired. IQ, omega-3 index, and premorbid adjustment were associated with class membership, whereas clinical variables (symptoms, substance use), including transition to psychosis, were not. Working memory and verbal learning and memory trajectory class membership was associated with functioning outcomes. These findings suggest there is no short-term progressive cognitive decline in help-seeking UHR individuals, including those who transition to psychosis. Screening of cognitive performance may be useful for identifying UHR individuals who may benefit from targeted cognitive interventions.